Triple negative status and BRCA mutations in contralateral breast cancer: a population-based study - Pellegrino, Benedetta; Bella, Mariangela; Michiara, Maria; Zanelli, Paola; Naldi, Nadia; Porzio, Rosa; Bortesi, Beatrice; Boggiani, Daniela; Zanoni, Daniele; Camisa, Roberta; Neri, Tauro Maria; Pinto, Carmine; et al. (Acta Biomedica Atenei Parmensis, 2016)
Background and aim of the work: BRCA1/2 mutation carriers diagnosed with breast cancer have a strong life-time risk of developing contralateral breast cancer (CBC). We performed a population-based study with the aim of estimating the proportion of CBC associated with BRCA1/BRCA2 mutations, and the contribution of germline mutations to both molecular and clinical features of these tumors. Methods: Fifty-five women with invasive CBC consecutively seen at the at the Genetic Oncology Service of the University Hospital of Parma from 2000 to 2011 were subjected to BRCA1/2 testing. Fifty-five case-matched, unilateral breast cancer (UBC) patients (pts), which tested negative for BRCA1/2 mutations, were selected as control group. Results: BRCA mutations were detected in 13 (24%) of 55 CBC pts. Women with BRCA1 mutations, and to a lesser extent BRCA2 mutations, were significantly more likely to present with high histologic grade, negative hormone receptor status and high proliferation rate in both first and second primary breast cancers than BRCA-negative, CBC tumors. A diagnosis of triple-negative breast cancer (TNBC) was significantly more frequent in women with BRCA mutations in comparison with BRCA-negative, UBC controls. There were no survival differences between BRCA-positive and non-BRCA tumors. Conclusions: Results of the present study indicate that both first primary and second primary breast cancers in BRCA carriers are qualitatively distinct from BRCA negative CBC, and from sporadic UBC controls. These findings highlight relevant clinical considerations about the potential value of BRCA testing in women with CBC as well as therapeutic, preventive, and surveillance implications for patients carrying a mutation.